Preparation and Anti-Icing of Hydrophobic Polypyrrole Coatings on Wind Turbine Blade - Bin Qu; Zhou Sun; Fang Feng; Yan Li; Guoqiang Tong; Rana Shahzad Noor (International Journal of Rotating Machinery)
This paper describes the method of preparing strong hydrophobic polypyrrole (PPy) on wind turbine blades. The water contact angle of strong hydrophobic PPy coatings was 127.2°. The strong hydrophobic PPy coatings exhibited excellent anti-icing properties. The maximum icing weight of strong hydrophobic PPy coating blade was almost 0.10 g while the maximum icing weight of no coating blade was found to be 26.13 g. The maximum icing thickness of a strong hydrophobic PPy coating blade was only 1.08 mm. The current research will provide a better technique to create anti-icing coatings on wind turbine blades and other outdoor equipment.